Helping yourself help others : a book for caregivers - Carter, Rosalynn; Golant, Susan K. (The University of Arkansas Press, 2023)
"In Helping Yourself Help Others, former first lady Rosalynn Carter draws upon her own experiences and those of hundreds of others to offer reassuring, practical advice to caregivers. Long before the COVID-19 pandemic inspired national conversations about the vast undervaluing of unpaid caregiving, the dangers of burnout, and the merits of self-care for relief, Rosalynn Carter was shining a light on these matters and everything else that caregivers confront"--